PICKY EATER PADA ANAK KOTA: STUDI KASUS ANAK USIA 3-4 TAHUN - Utami, Fitria Budi (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2016)
The objective of this research is to find description of picky eater in city ages 3-4 years old. This research was conducted at Nursery B Class of TK Ananda Islamic School Jakarta, on January-March 2015. There are five sub focues was discussed, those are: (1) characteristic of young child picky eater; (2) the causes of picky eater; (3) the roles of family; (4) teachers handling; (5) the effects of picky eater in children. It was qualitative research by case study. The data were collected through participant observation, interview, and documentation. Data technic analysis was Miles and Huberman model. The results indicate that: (1) The characteristic of young child with picky eater are rejection of specific familiar foods and new foods (food neophobia); (2) The reasons are allergic, unaproppiate MPASI, and parents worried to interdiction new food for child; (3) the roles of family are the parents aware so they bring the child to the doctor, give vitamin, change the menu and make a new eaten schedule; (4) The teachers handling are give the children about nutrition’s education, give reward and make a good communication to parents; (5) The effect of picky eater is the children easy infected by germs.